CTENOCLERUS, NUEVO GÉNERO ENDÉMICO DE LA REGIÓN MEDITERRÁNEA DE CHILE (COLEOPTERA: CLERIDAE: CLERINAE) - Solervicens A., Jaime (Acta Entomológica Chilena, 2022)
Ctenoclerus, a new genus and two new species, C. lineatus and C. pectinatus, are described. The genus is classified in the subfamily Clerinae, near Notocymatodera Schenkling; its geographic distribution in the mediterranean zone of Chile is recognized. Figures and a key for identification of the species are provided.